Games, Attention and Brain Signals (2021)
This paper shows the development of software that contains educational games, and integrates a NeuroSky sensor, which allows the detection of brain waves. The system was developed in Matlab, and allows real-time storage of the brain signal determining the levels of attention while the child interacts with the game. The tests carried out made it possible to determine what type of games generated more attention in children, which would allow in future work to adapt information taking into account the student’s profile and achieving improvements in the teaching and learning process.